Coexistence Mechanism for Colocated HDR/LDR WPANs Air Interfaces. (5th October 2010) - Monti, Marco; De Sanctis, Mauro; Cianca, Ernestina; Ruggieri, Marina; Prasad, Ramjee
Abstract : This paper addresses the issues of interference management among Low Data Rate (LDR) and High Data Rate (HDR) WPAN air interfaces that are located in close-proximity (up to 10 cm) and eventually on the same multimode device. After showing the noticeable performance degradation in terms of Bit Error Rate (BER) and goodput due to the out-of-band interference of an HDR air interface over an LDR air interface, the paper presents a novel coexistence mechanism, named Alternating Wireless Activity (AWA), which is shown to greatly improve the performance in terms of goodput of the most interference vulnerable air interface (i.e., the LDR air interface). The main difference of the proposed mechanism with respect to other collaborative mechanisms based on time-scheduling is that it synchronizes the transmission of the LDR and HDR WPANs at the superframe level instead of packet level. Advantages and limitations of this choice are presented in the paper. Furthermore the functionalities of the AWA mechanism are positioned in a common protocol layer over the Medium Access Control (MAC) sublayers of the HDR and LDR devices and it can be used with any standard whose MAC is based on a superframe structure.